Firmly Adsorbed Ammonia and Pyridine Species at Activated Kaolinite Surfaces - Tabak Ahmet; Afsin Beytullah (Adsorption Science & Technology)
Acid activation increases the protonated species on a kaolinite surface at the expense of coordinately bound NH 3 entities. The presence of NH + 4 ions on an activated sample is not proof of the presence of protonic acid centres alone since the added proton may have come from the residual water in the interlayer. Progressive dehydration of the surface results in a strong increase in chemisorbed NH 3 . However, the ‘ring frequency’ region of coordinately bound pyridine (Py) and of the pyridiniumion (Py + ) indicates that the strong acid sites on activated kaolinite are of the Lewis type.